Pengaruh Serbuk Kaca Sebagai Substitusi Parsial Semen terhadap Kuat Tekan Beton Alir - Arsasuta, Faris; Rochmah, Nurul (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
AbstractIn the current construction development, concrete is the main material used because of its advantages in strength and durability. One of the innovations in the use of concrete is flow concrete, which allows use without compactors and has optimal viscosity. The use of glass powder as a partial substitution of cement is an attractive alternative because of its potential in improving concrete properties. Glass powder has a fairly large silica (SiO2) content of 75%. Silica has a strong relationship with the compressive strength of concrete. Proper silica in concrete mix can increase the compressive strength of concrete. This study aims to determine the effect of glass powder with variations of 0%, 6%, 8%, 10%, 12% on the compressive strength of flow concrete with a proportion of superplasticizer 1.5%. Compressive strength testing is carried out when concrete reaches the age of 7, 21, 28 days using cylindrical specimens measuring 15 × 30 cm. From the test results, the highest compressive strength value was obtained at 28 days concrete age, namely in an 8% glass powder mixture of 25.61 Mpa and the lowest compressive strength value in a 12% glass powder mixture of 21.26 Mpa. Based on the results of this study, it can be concluded that glass powder as a partial substitution of cement can increase the compressive strength of flow concrete with an optimal glass powder mixture of 8%. Keywords— Flowing Concrete, Glass Powder, Compressive Strength